Association Between Glycated Albumin, Fructosamine, and HbA1c with Neonatal Outcomes in a Prospective Cohort of Women with Gestational Diabetes Mellitus - Mendes, N (2019)
Objective: To investigate whether glycated albumin, fructosamine, and hemoglobin A1c (HbA1c) are associated with neonatal complications in newborns of pregnant women with gestational diabetes mellitus (GDM). Methods: Between November 2016 and September 2017, women with a singleton pregnancy and GDM were enrolled in a prospective study in an obstetric Portuguese referral center. Glycemic markers were compared between mothers of newborns with and without complications. Multivariable logistic regression models and corresponding areas under the receiver operating characteristic curve (AUC) were used. Results: A total of 85 women participated in the study. Raised levels of glycated albumin and fructosamine were associated with at least one neonatal complication (OR- [odds ratio] estimate: 1.33, P=0.015; OR: 1.24, P=0.027, respectively) and with respiratory disorders at birth (OR 1.41, P=0.004; OR 1.26, P=0.014, respectively). HbA1c was not associated with these outcomes. All biomarkers were associated with large-for-gestational age (LGA) status (OR 1.61, P<0.001; OR 1.45, P<0.001; OR 3.62, P=0.032 for glycated albumin, fructosamine, and HbA1c, respectively). All had similar AUC for at least one neonatal complication (0.82; 0.81; 0.79, respectively). For newborn respiratory disorders, AUCs were 0.83, 0.81, and 0.76, respectively, and for LGA status were 0.81, 0.79, and 0.71, respectively. Conclusion: Raised values of glycated albumin and fructosamine were associated with particular perinatal complications in newborns of mothers with GDM, better discriminating mothers of newborns with and without complications than HbA1c.